(untitled) (Revista Latino-Americana de Enfermagem, 2008)
OBJECTIVE: To identify factors that delay the onset of thrombolysis in patients with acute myocardial infarction (AMI). METHODS: A cohort study was carried out with 146 patients, each diagnosed with AMI and subjected to thrombolytic therapy. The data was extracted from medical records between January 2002 and December 2004. RESULTS: The average age of the studied population was 57.5 ± 9 years, 64.4% were male. The average time between the onset of pain and arrival at the hospital was 254.7 ± 126.6 minutes, 28.1% used an ambulance for the trip to the hospital, the door-to-electrocardiogram time averaged 19.4 ± 7.3 minutes and the door-to-needle time was 51.1 ± 14.9 minutes. There was no significant difference between the time of arrival to the hospital and the method of transportation used (P= 0.81), and those seen by cardiologists and during the nightshift had a reduction in the door-to-needle time, respectively (P=0.014) and (P=0.034). CONCLUSIONS: Study results show that the delay in the search for medical service, and the long time taken from door-to-electrocardiogram and to reach the AMI diagnosis were the factors involved in the delay of thrombolytic treatment.